Pengaruh Terapi Okupasi terhadap Gejala Halusinasi Pendengaran Pada Pasien Halusinasi Pendengaran Rawat Inap di Yayasan Aulia Rahma Kemiling Bandar Lampung - Niken Yuniar Fitri (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
Hallucinations are an experience of one or the wrong response to sensory stimulation. One of the management of hospitals with hallucinations is occupational therapy.This study aims to determine the frequency distribution of auditory hallucinatory symptoms in auditory hallucinatory patients. Using the quasi experiment pre-post test without control group design. A total of 27 samples were selected by total sampling technique, a valid and reliable instrument. The analysis uses dependent t test. The results showed hallucinations symptoms decreased after being given occupational therapy. (p-value <α 0.05), the frequency of auditory hallucinations symptoms experienced by auditory hallucinations clients before being given the most occupational therapy in the medium category (51.9%). After being given the most auditory hallucinations symptom therapy in the mild category (44.4%) Occupational therapy is recommended to treat hallucinations in clients with auditory hallucinations.